THE IMPLEMENTATION OF THE SCHOOL UNIT MANAGEMENT AUTONOMY PROGRAM – PAGUE – IN THE TEFÉ REGIONAL EDUCATION COORDINATION OFFICE - Mendes da Costa, Iberson; Eugenia Gonzalez Chena, Ana (Revista Gênero e Interdisciplinaridade, 2025)
The School Unit Management Autonomy Program (PAGUE) is a public policy of financial decentralization implemented in the State of Amazonas. This study analyzes its implementation in the Tefé Regional Education Coordination (CRET), considering advances, challenges, and perceptions of the main actors involved, such as school administrators and/or members of the APMCs/School Councils. The program is based on the development of application plans, community approval, and rigorous accountability. The general objective of this research was to analyze the implementation process of PAGUE, identifying the main challenges faced by state schools in Tefé. The methodology used was a qualitative case study. Data were initially collected through documentary and bibliographic research, characterized by an exploratory data collection in available literary materials. Subsequently, semi-structured interviews were conducted with current school administrators, in addition to a questionnaire with structured questions applied to former administrators or members of APMCs. The participation of APMCs (Parents, Teachers, and Community Associations) or School Councils in the decision-making process revealed regional disparities, highlighting the need for greater community engagement and qualification. It is concluded that the success of PAGUE (Program for the Modernization of Educational Management) is contingent upon alignment with regional demands, continuous training, and investments in basic and technological infrastructure. The program presents significant potential to modernize educational management in Amazonas, promoting greater equity and efficiency in resource allocation.